تحسين كفاءة مراجل أنابيب اللهب باستخدام تقنيات متعددة (Latakia University Journal -Engineering Sciences Series, 2019)
في ظل الطلب العالمي المتزايد على الطاقة، وارتفاع أسعار النفط أصبحت عمليات الحد من الهدر، وتوفير الطاقة من خلال تحسين كفاءة مراجل البخار حاجة ملحة، وضرورية، لهذا تم انجاز عدد من الاختبارات على عدد من مراجل أنابيب اللهب العاملة في الصناعة السورية بغرض تحسين كفاءتها، حيث تم استبدال فالات تذرير الوقود، واستخدام تقنيات الصفيحة المثقبة، وأسلاك التدويم، لتحسين عمليات المزج داخل حجرة الاحتراق وانتقال الحرارة إلى وسيط التشغيل، وقد أظهرت النتائج أن كفاءة مرجل أنبوب اللهب المختبر، تحسنت عند استبدال فالة التذرير القديمة بأخرى جديدة بحوالي 6%، كما تحسنت الكفاءة بنتيجة استخدام الصفيحة المثقبة، بالمقارنة مع استخدام نظام التدويم الحلقي، بحوالي 5%. أما في حالة استخدام أسلاك التدويم في أنابيب مساري غازات الاحتراق الأول، والثاني، فقد أدى ذلك إلى رفع الكفاءة بما يتجاوز 2 %.  ما يعني وفراً سنوياً وسطياً يتراوح مقداره بين 4 و6.5 مليوناً ل.س في السنة لكل مرجل، وذلك بحسب إجمالي استهلاك المرجل السنوي من الوقود المرتبط بصورة رئيسة بزمن التشغيل وباستطاعة المرجل، وبافتراض أن سعر الفيول يبلغ 13000 ل.س/طن. With the ever increasing world requirement to the power and the high cost of fuel, the losses reducing and saving processes became very important through improving the boiler efficiency. Therefore, the number of tests are performed on some of fire tube boilers used in industrial public sectors to improve their efficiency. The old atomizing nozzle is replaced. Also,  the perforated plate and swirler coil wires are used to improve the mixing process  inside the combustion chamber and increasing the heat transfer to working media. The boiler efficiency has been improved by replacing old atomizing nozzle by other new at excess air ratio about 30.% by 6.%, and the efficiency improved by using the perforated plate in comparison with using the swirler desk system at excess air ratio about 24% by 5%. In state of swirler coil wires using in first and second gas tubes paths, the efficiency increased by 2% at excess air ratio 40%. On the other hand,  that means, the boiler efficiency improvements will allow to earn between 4 and 6.5 million S.P. yearly for each boiler according to fuel consumption of boilers, which mainly related to the period of operation and the capacity of boiler; that is, by assuming that the cost of fuel is about 13000 S.P./ton.